2021
DOI: 10.3390/molecules26020492
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Natural Compounds as Potential PI3K-AKT1 Signaling Pathway Inhibitors and Experimental Validation

Abstract: A computational screening for natural compounds suitable to bind the AKT protein has been performed after the generation of a pharmacophore model based on the experimental structure of AKT1 complexed with IQO, a well-known inhibitor. The compounds resulted as being most suitable from the screening have been further investigated by molecular docking, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) analysis and toxicity profiles. Two compounds selected at the end of the computational analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…In AKT1, the docking result of the two forms of curcumin was compared to that of the original ligand, AKT1 inhibitor (IQO), in the selected AKT1 structure (PDB ID: 3O96) ( Table 3 ) [ 10 ]. The AKT1 inhibitor shows a very low binding energy of <−14.0 Kcal/mol and curcumin also shows reasonable binding energy of <−9.0 Kcal/mol, compared to the previously published docking study [ 15 ].…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…In AKT1, the docking result of the two forms of curcumin was compared to that of the original ligand, AKT1 inhibitor (IQO), in the selected AKT1 structure (PDB ID: 3O96) ( Table 3 ) [ 10 ]. The AKT1 inhibitor shows a very low binding energy of <−14.0 Kcal/mol and curcumin also shows reasonable binding energy of <−9.0 Kcal/mol, compared to the previously published docking study [ 15 ].…”
Section: Resultssupporting
confidence: 55%
“…Moreover, our molecular docking study showed that, among the four identified targets, AKT1 showed the highest binding affinity for curcumin, indicating that AKT1 is the most potent target. The calculated binding energy of curcumin to AKT1 was reasonably low as <−9.0 Kcal/mol, indicating a possible inhibitory effect [ 15 ]. Lastly, our in vitro study demonstrated that curcumin was effective against influenza virus in both pre- and post-treatment paradigms, and confirmed inhibition of mRNA level of AKT expression suggesting that curcumin could be useful as either a prophylactic or therapeutic influenza agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scenario, we recently completed a computational screening to search for compounds that are able to bind the AKT protein by generating a pharmacophore model based on the experimental structure of AKT-1 in complex with IQO, a well-known AKT-1 inhibitor. We selected two compounds, ZINC2429155 (STL1) ( Figure 1 b) and ZINC1447881 (AC1) both suitable in silico to bind AKT-1 in an allosteric site, but only one, STL1, was able in vitro to reduce Ser473 phosphorylation, thus inhibiting the PI 3 K/AKT pathway [ 7 ]. However, the inactivation of AKT phosphorylation by STL1 was not sufficient to induce cell death in the malignant cell line investigated as represented by the HG-3 cells, a lymphoblastoid cell line with B1 cell characteristics established from a CLL clone by the in vitro EBV infection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%